Upper limb injury in rugby union football: results of a cohort study - Usman, J.; McIntosh, A.S. (2012)
BACKGROUND: There have been few in-depth studies of upper limb injury epidemiology in rugby union football, despite reports that they accounted for between 14 and 28 of all rugby injuries. OBJECTIVE: To report on upper limb injury incidence, injury severity and to identify the risk factors associated with upper limb injuries, for example, level of play, season (years) and playing position. DESIGN: Prospective cohort study across five rugby seasons from 2004 to 2008. SETTING: Formal rugby competitions-suburban, provincial and international. PARTICIPANTS: 1475 adult male rugby players in Colts, Grade and Elite competitions. MAIN OUTCOME MEASUREMENTS: An upper limb injury resulting in a missed game and its characteristics. RESULTS: A total of 61 598 athletic exposures (AE) and 606 upper limb injuries were recorded. About 66 of the injuries were to the shoulder. The overall upper limb injury incidence rate (IIR) was 9.84 injuries/1000 AE (95 CI 9.06 to 10.62). Statistically significant associations were found between upper limb injuries and level of play; and between shoulder injuries and playing position (p<0.05). No association was found between upper limb and shoulder injuries and study year. The overall upper limb IIR decreased as the level of play increased; 10.74 upper limb injuries/1000 AE (95 CI 9.93 to 11.56) in Colts to 6.07 upper limb injuries/1000 AE (95 CI 5.46 to 6.69) in Elite. CONCLUSIONS: The upper limb IIR decreased as the level of play increased indicating that age, level of skill and playing experience may be risk factors for upper limb injury.